2012
DOI: 10.5194/se-3-433-2012
|View full text |Cite
|
Sign up to set email alerts
|

Bromine monoxide / sulphur dioxide ratios in relation to volcanological observations at Mt. Etna 2006–2009

Abstract: Abstract. Over a 3-yr period, from 2006 to 2009, frequent scattered sunlight DOAS measurements were conducted at Mt. Etna at a distance of around 6 km downwind from the summit craters. During the same period and in addition to these measurements, volcanic observations were made by regularly visiting various parts of Mt. Etna. Here, results from these measurements and observations are presented and their relation is discussed. The focus of the investigation is the bromine monoxide/sulphur dioxide (BrO / SO2) r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 48 publications
2
42
1
Order By: Relevance
“…The halogen chemistry is of especially great interest as BrO / SO 2 ratios in volcanic plumes are readily measurable by remote sensing UV spectrometry (e.g., Bobrowski et al, 2003;Lübcke et al, 2014) and have been discussed in recent years as another potential precursory observable parameter for volcanic activity changes. Although several studies observed decreases in the BrO / SO 2 ratio before eruptive phases (e.g., Lübcke et al, 2014) and lower ratios during periods of continuous activity (Bobrowski and Giuffrida, 2012), it is not yet clear whether magma-gas partitioning of bromine occurs before or after sulfur during the pressure drop associated with magma ascents (Dinger et al, 2018). Furthermore, BrO is not a directly emitted species; rather it is the product of complex heterogeneous chemistry in the volcanic plume involving reactions with magmatic gases with entrained air (e.g., Gerlach, 2004;Bobrowski et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The halogen chemistry is of especially great interest as BrO / SO 2 ratios in volcanic plumes are readily measurable by remote sensing UV spectrometry (e.g., Bobrowski et al, 2003;Lübcke et al, 2014) and have been discussed in recent years as another potential precursory observable parameter for volcanic activity changes. Although several studies observed decreases in the BrO / SO 2 ratio before eruptive phases (e.g., Lübcke et al, 2014) and lower ratios during periods of continuous activity (Bobrowski and Giuffrida, 2012), it is not yet clear whether magma-gas partitioning of bromine occurs before or after sulfur during the pressure drop associated with magma ascents (Dinger et al, 2018). Furthermore, BrO is not a directly emitted species; rather it is the product of complex heterogeneous chemistry in the volcanic plume involving reactions with magmatic gases with entrained air (e.g., Gerlach, 2004;Bobrowski et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the magma degassing behavior and/or the hydrothermal systems beneath volcanoes generally influence the gas composition and gas fluxes. Measuring the emitted gas composition can provide crucial information on understanding subsurface processes related to activity changes (e.g., Allard et al, 1991;Aiuppa et al, 2007;Bobrowski and Giuffrida, 2012;de Moor et al, 2016a;Liotta et al, 2017) and help to estimate fluxes of the geological carbon cycle (e.g., Burton et al, 2013;Mason et al, 2017) and tectonic processes controlling volcanic degassing (e.g., Aiuppa et al, 2017;de Moor et al 2017). In the field of volcanic monitoring, the observation of gas composition changes has become an important tool for detecting precursory processes for volcanic eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion rate or even the stationary state ratio between HBr and BrO may depend on the plume composition and the atmospheric conditions (meteorology) (Roberts et al, 2014) and thus on parameters like solar irradiance, air temperature, air pressure, or relative hu-35 midity. However, Bobrowski and Giuffrida (2012) have not found a correlation between BrO and the relative humidity or the wind speed, which poses the question if the bromine explosion in volcanic gas plumes is indeed significantly depending on the meteorological conditions or not.…”
Section: −3mentioning
confidence: 99%
“…Accordingly, even under the assumption that the HBr/SO 2 degassing ratio is purely pressure-dependent no quantitative deduction of the pressure change could be made based on BrO/SO 2 molar ratios. Further, it was even not yet possible to derive the sign of this correlation indirectly by empirical studies of BrO/SO 2 molar ratios simultaneously to pressure changes 15 (Bobrowski and Giuffrida (2012), Lübcke et al (2014)) because of the still limited data sets available. In the absence of an explicit interpretation of the BrO/SO 2 molar ratio, at least the reasoning that a change in BrO/SO 2 molar ratios is probably caused by a significant change in magmatic conditions appears to be nevertheless a reasonable hypothesis.…”
Section: Comparison Of Bro/so 2 Time Series With Meteorologymentioning
confidence: 99%
See 1 more Smart Citation